Economic perspectives on agricultural and natural resources policy - Quilloy, Antonio Jesus A.
Agricultural and natural resources policy involves an intricate balance of political, social, and environmental choices where the principles of economics may serve as guide in various aspects of public decision making and policy design. Economics does not hold a monopology of knowledge about the analytics and operational mechanisms of agricultural and natural resources policy, but the insights that we can draw by applying economic principles on agricultural and natural resources policy problems are compelling and logical. This book provides economic perspectives on agricultural and natural resources policy and tries to isolate the economics component by analyzing the incentives and the economic consequences that public policy creates.